2010
DOI: 10.1016/j.molimm.2010.06.014
|View full text |Cite
|
Sign up to set email alerts
|

SARS spike protein induces phenotypic conversion of human B cells to macrophage-like cells

Abstract: Massive aggregations of macrophages are frequently detected in afflicted lungs of patients with severe acute respiratory syndrome-associated coronavirus (SARS-CoV) infection. In vitro, ectopic expression of transcription factors, in particular CCAAT/enhancer-binding protein alpha (C/EBPα) and C/EBPβ, can convert B cells into functional macrophages. However, little is known about the specific ligands responsible for such phenotype conversion. Here, we investigated whether spike protein of SARS-CoV can act as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 46 publications
2
16
0
Order By: Relevance
“…Infection with the severe acute respiratory syndrome (SARS) coronavirus, the causal agent of SARS, results in a significant accumulation of enlarged M2 macrophages in the lung 32. Spike (S) protein, a major structural component of SARS, induces the conversion of B cells into cells that resemble macrophages, when displayed on recombinant baculovirus 33. Dosch et al 34 showed that secreted S protein could activate blood monocytes via TLR2.…”
Section: Macrophage Mediation Of Airway Diseasementioning
confidence: 99%
“…Infection with the severe acute respiratory syndrome (SARS) coronavirus, the causal agent of SARS, results in a significant accumulation of enlarged M2 macrophages in the lung 32. Spike (S) protein, a major structural component of SARS, induces the conversion of B cells into cells that resemble macrophages, when displayed on recombinant baculovirus 33. Dosch et al 34 showed that secreted S protein could activate blood monocytes via TLR2.…”
Section: Macrophage Mediation Of Airway Diseasementioning
confidence: 99%
“…Monocytes/macrophages have also been implicated in SARS-CoV disease pathogenesis (8,38). In SARS-CoV patients, infiltrating monocytes/macrophages have been shown to persist long after the virus has been eradicated from the lung, and the excessive accumulation of these cells is a prominent pathological feature in most SARS-CoV autopsy cases (9).…”
mentioning
confidence: 99%
“…The origin of the structures identified in the present study is not likely to be phagosomes, because B lymphocytes are not generally capable of phagocytosis. 18 In addition, the cells were not challenged with an external pathogen, and phagocytic activity was not observed by electron microscopy.…”
Section: Discussionmentioning
confidence: 99%